The Representation Of Syrian Refugees In The Online Media News Reports Of Host And Non-Host Countries: A Corpus-Based Critical Discourse Analysis - Abid, Raith Zeher (2015)

(untitled)
Terdapat banyak kajian yang telah meneliti pemaparan media tentang pelarian di negara tuan rumah. Namun begitu, tidak banyak kajian yang memberikan perhatian kepada pemaparan ini di negara bukan tuan rumah. Kajian ini memanfaatkan teori kategori sosial wacana oleh Van Leeuwen (2008) khasnya “role allocation”, “genericisation dan specification”, “assimilation”, “association”, “indetermination”, dan “identification” serta metafora konsepsi saranan Lakoff dan Johnson (2003) untuk mengkaji pemaparan media tentang pelarian Syria di negara tuan rumah dan di negara bukan tuan rumah. Linguistik korpus diguna pakai untuk memastikan hasil kajian ini menyeluruh, sah dan saksama. Korpora kajian ini mengandungi 3082130 perkataan. Program Anthony AntConc (versi 3.2.4) digunakan untuk menganalisis korpora ini. Untuk menghitung signifikan statistik pula, Ujian Ketepatan Fisher (Fisher Exact Test) dimanfaatkan. There is a substantial body of research that has examined the media representation of refugees in their host countries. However, scant attention has been paid to their depiction in the media discourse of non-host countries. This study uses Van Leeuwen‟s (2008) sociological categories of discourse, namely role allocation, genericisation and specification, assimilation, association, indetermination, and identification, as well as Lakoff and Johnson‟s (2003) conceptual metaphor theory to examine the representation of Syrian refugees in the online media news reports of both their host and non-host countries. Corpus linguistics is used to ensure that the results are generalizable, valid, and impartial. The two corpora of this research consist of 3082130 words. Anthony‟s AntConc programme (version 3.2.4) was used to analyse the corpora. To calculate the statistical significance in comparing both corpora, Fisher‟s exact test is used.